A systematic survey of plant biodiversity study within the land of Institut Teknologi Sumatera (ITERA) - I. Oktaviani; M. Asril; Y. Aryanti; S. S. Leksikowati (Journal of Science and Applicative Technology, 2019)
The conversion of agricultural land and plantation into an area with high human activity can affect the biodiversity contained in it. The biodiversity of a region can be surveyed and collect in a systematic database to know the wealth of flora and fauna resources within a certain period of time. The aim of this research is to identify and inventory the vegetation database of plant, which can then be used as one of the important information related to the environmental change that happened from time to time following the impact of the growing development expansion. This study was conducted within the campus of the Institut Teknologi Sumatra (ITERA) which is undergoing physical construction in the form of buildings, roads, and some retention basin. Data retrieval was done by direct observation using the cruising method. The observations of each species are documented, identified, recorded and arranged in the collection catalog.